Avaliação da carga microbiana e fúngica de sistemas de canais radiculares infectados e a expressão apical de integrinas, citocinas e quimiocinas nos tecidos perirradiculares adjacentes - Wilson Bambirra Júnior (2022)
This study seeks to quantitatively evaluate the expression of messenger RNA (mRNA) of integrins alpha1, alfa4, alpha 5, alpha L, cytokines, and chemokines, from cells present in the periapical interstitial fluid adjacent to teeth with root canal infection. Twenty-two individuals needing endodontic treatment and referred to the School of Dentistry of the Federal University of Minas Gerais (Belo Horizonte, MG, Brazil) were selected. The samples were collected in 11 necrotic teeth and carriers of endodontic infections and 11 healthy teeth needing endodontic treatment for prosthetic reasons. After access surgery and before root canal system (RCS) cleaning and shaping procedures (T0), immediately after cleaning and shaping the root canal system (T1), in 7 (T2) and 14 days (T3) an endodontic sterilized paper point #20 was inserted into the RCS, maintained for 2 min, and subsequently stored at -70°C. Real-Time PCR microbiologically analyzed these samples to read the gene expression of microbial rRNA 16S and fragments of the ITS region of the Fungus Candida species gDNA. After RCS cleaning and shaping procedures, three sterilized absorbent paper cones were inserted. Passively, the paper point exceeded the root apex by 2 mm and remained for 2 minutes. Samples were collected immediately after RCS cleaning and shaping, 7 and 14 days after the first session. The paper points have the 4 mm of their tip cut, inserted in Eppendorf, and stored at - 70°C. This procedure extracted RNA from the periapical interstitial fluid to characterize the expressions of the genes ITGA1, ITGA4, ITGA5, ITGAL, IL-1β, TNF- α, IL-17A, IL-10, IFN-γ, CCL2/MCP-1, CCL5, CXCR4, ITS using Real-Time PCR. The results showed that 16S mRNA expression levels decreased after cleaning and modeling procedures and that Candida abundance was incipient in the analyzed sample. Pro-inflammatory cytokines IL-1β and IL-17 showed high expression levels against infection, significantly reduced after cleaning and formatting procedures. TNF-α gene expression levels significantly increased in both experimental and control groups. No significant difference was observed regarding the gene expression of the cytokines IFN-γ, IL-10, CCL-2, and CCL-5 and the integrins ITGAL and ITGA5. The gene expressions of ITGA1 and ITGA4 in the experimental group were significantly reduced time-dependent. Finally, there was no significant change in their macrophage markers (CD64) expression, while fibroblast markers (S100A4) expression significantly increased in the control group. It was concluded that microbial load and yeast abundance are positively correlated with the expression of pro-inflammatory mediators and that endodontic therapy negatively impacts the expression of pro-inflammatory mediators and integrins in periradicular tissues